Segunda cita de Colibri thalassinus para la Argentina - Bertelli, Sara (1997)
A Green Violetear Colibri thalassinus was mistnetted in Alnus acuminata forest at Catamarca province, northwestem Argentina. The previous record for this hummingbird was Olrog (1963) for Tucumán province. The individual captured was an adult, with neither molt nor brood patch.